Hubungan Antara Tingkat Kecemasan dengan Hasil Belajar Guling Belakang pada Siswa SMP: Analisis Berdasarkan Jenis Kelamin - Annisa Dwi Januari; Yusuf Hidayat; Asep Sumpena (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between anxiety levels and backward roll learning outcomes in junior high school students, as well as to examine differences based on gender. This study employed a correlational design with a quantitative approach and random sampling technique, involving 105 students consisting of 49 male students and 56 female students. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), which has passed validity and reliability tests, while backward roll learning outcomes were measured through practical skills assessment using an established assessment rubric. The Kolmogorov-Smirnov normality test showed that the data were not normally distributed. Therefore, Spearman's Rank correlation test was used for correlation analysis, and the Mann-Whitney U Test was used for gender-based difference analysis. The results indicated that there was no significant relationship between anxiety levels and backward roll learning outcomes (ρ = -0.131; p = 0.181 > 0.05). However, there was a significant difference in anxiety levels between male and female students, with female students showing higher anxiety levels (Mean Rank = 72.08; p = 0.000 < 0.05). It was concluded that gender influences the anxiety levels of junior high school students. Thus, managing psychological aspects through learning strategies that can increase self-confidence and create a conducive learning environment is an important factor in supporting the success of floor gymnastics learning. Keywords: Gender, Backward Roll, Anxiety, Floor Gymnastics, Junior High School Students